PENGARUH UKURAN PERUSAHAAN, UMUR OPERASIONAL, DAN CAPITAL ADEQUACY RATIO (CAR) TERHADAP KEMAMPULABAAN LPD - Siswandari, Agung Mirah; Putra, I Wayan (E-Jurnal Akuntansi; Vol 19 No 3 (2017), 2017)
Economy in Bali currently is increasingly showing significant improvement. LPD would facilitate the public in obtaining the financial resources to their needs whether they are productive and consumption. One of indicators to assess the health of LPD is Profitability. Gains derived by a financial institution is strongly influenced by its human resources to manage and process the existing financial resources.  This report aims to understand influence the size of the company, operational age, and capital adequacy ratio ( car ) against LPD profitability. The total sample research obtained by 73 LPD with the probability of sampling and engineering proportionate stratified random sampling. Analysis techniques the data used analytics multiple linear regression. The results show operational age have a significant negative impact on LPD profitability while the size of the company and capital adequacy ratio ( car ) have significant positive impact on profitability LPD .
Keywords: size of company, operational age, capital adequacy ratio (CAR), profitability